An expanded view of viruses: editorial - Greber, Urs F.; Bartenschlager, Ralf (FEMS microbiology reviews, 2017)
Viruses are ubiquitous, and are important in medicine, biology, biotechnology and ecology. All kinds of cells can be infected with viruses, and sometimes, a par